2004
DOI: 10.1016/j.yebeh.2004.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate in clinical practice: long-term experience in patients with refractory epilepsy referred to a tertiary epilepsy center

Abstract: For the treatment of patients with chronic refractory epilepsies, information about the long-term efficacy and safety profile of any new antiepileptic drug is crucial. Topiramate has been proven to be effective in patients with refractory chronic partial epilepsies in short-term controlled clinical trials, but the long-term retention, long-term efficacy, and long-term side-effect profile have not been sufficiently investigated. We analyzed all patients who had been treated with topiramate in the Epilepsy Centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
3
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 10 publications
3
50
3
8
Order By: Relevance
“…In general, the cognitive effects of AEDs are less than the sum total of other factors and are usually reversible. [34] R. Thomas et al [35] examined 60 patients with drugrefractory JME and concluded that patients were profoundly impaired across the range of tests evaluating intellectual function, memory, language and naming, executive function, the impact of epilepsy, and AED side effects. Eighty-three percent of patients exhibited frank executive dysfunction, which was moderate to severe in 66%.…”
Section: Adverse Side Effects Of Antiepileptic Drugsmentioning
confidence: 99%
“…In general, the cognitive effects of AEDs are less than the sum total of other factors and are usually reversible. [34] R. Thomas et al [35] examined 60 patients with drugrefractory JME and concluded that patients were profoundly impaired across the range of tests evaluating intellectual function, memory, language and naming, executive function, the impact of epilepsy, and AED side effects. Eighty-three percent of patients exhibited frank executive dysfunction, which was moderate to severe in 66%.…”
Section: Adverse Side Effects Of Antiepileptic Drugsmentioning
confidence: 99%
“…Cognitive complaints, related to confirmed cognitive dysfunction has been reported with almost all the older drugs and especially for phenobarbital (PB), phenytoin (PHT) and vigabatrin (VGB) [4,5]. Some newer AEDs such as topiramate (TPM) and zonisamide (ZNS) are also known to cause significant cognitive side-effects: both have diffuse cognitive effects, as well as specific effects on language and memory [5][6][7][8][9]. This concurs with the patient-reported cognitive side-effects that are more common with TPM, followed by ZNS and phenytoin (PHT) and are least likely to be reported with GBP, valproate (VPA), LTG and carbamazepine (CBZ) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Особого внимания заслуживают препараты группы топирамата (ТПМ), вызывающие дозозависимые речевые нарушения, расстройства памяти и внимания [19], но в то же время ТПМ обладает антидепрессивным действием при условии медленной титрации [20]. Однако удержание на те-рапии через 4 года, по данным H.P.…”
unclassified
“…Bootsma и соавт. [19], со-ставляет 30%; при этом в половине случаев отказом от лече-ния послужили когнитивные расстройства, снижающие ка-чество жизни пациентов. Препараты группы леветирацета-ма (ЛЕВ), по данным большинства исследователей, не ока-зывают неблагоприятного действия на когнитивные функ-ции [21][22][23], а препараты группы ламотриджина (ЛТД) и вальпроевой кислоты (ВК) улучшают память и оказывают нормотимическое действие как в моно-, так и в политера-пии [5,24].…”
unclassified